OPERATION «BROTHER’S KEEPER» IN CONTEXT OF THE PALESTINIAN-ISRAELI STANDOFF - V. M. Morozov; A. A. Ermakov (Vestnik MGIMO-Universiteta, 2016)
Nowadays the Gaza Strip radical movement HAMAS is the most dangerous opponent for the State of Israel in the Palestinian arena. In recent years most attention of the world community has been focused on the events in the Gaza Strip. This attention is caused by the dynamics of standoff and the scale of events occurred. During the period after authority setting in the Palestinian enclave by HAMAS movement Israel carried out a series of large-scale military operations. These were «Cast Lead», «Pillar of Defense» and «Protective Edge». However for better understanding of dynamics of the conflict between Israelis and Palestinians it is necessary to pay equal attention to confrontation both in the Gaza Strip and West Bank. In the article the authors study the events of June 2014 that were a part of the permanent standoff in the West Bank. In June 2014 after abduction of the three teenagers by radicals Israel carried out the operation «Brother's Keeper» which preceded the large-scale operation «Protective Edge». The actions of Israelis aimed at weakening the infrastructure of HAMAS. During the operation in the West Bank Israel used considerable forces. Israelis caused a painful blow to HAMAS. The results of the operation «Brother's Keeper» suggested that the radicals of the West Bank may get developed underground infrastructure and developed infrastructure for production of rockets. The events of summer 2014 in zone of the Palestinian- Israeli conflict showed that escalation may spread from one part of the Palestinian land to another.